2015
DOI: 10.1007/s11270-015-2381-y
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Platinum Nanoparticles by Sinapis alba and Lepidium sativum Plants

Abstract: Nanoparticles (NPs) are commonly used, and concerns about their possible adverse effects are being voiced as well. However, little is known about the fates of NPs released to the environment. The aim of the study was to (i) evaluate the ability of Sinapis alba and Lepidium sativum plants to take up platinum nanoparticles (Pt-NPs) and translocate them to aboveground organs, (ii) compare the accumulation efficiency of different forms of platinum and (iii) identify the forms in which platinum is stored in plant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Astafurova et al [101] reported enhanced plant protective mechanisms due to increased flavonoids concentration resulting from nanoplatinum application. In another study of platinum nanoparticles uptake using Sinapis alba and Lepidium sativum plants, both plant species showed uptake of considerable amounts in the roots and shoots at different concentrations [102]. In this study, both the metal salts and nanoparticles were bioavailable with no recorded phytotoxicity and the Sinapis alba plant recorded higher nanoparticles translocation with increasing concentration than Lepidium sativum.…”
Section: Noble Metal Nanoparticlesmentioning
confidence: 48%
“…Astafurova et al [101] reported enhanced plant protective mechanisms due to increased flavonoids concentration resulting from nanoplatinum application. In another study of platinum nanoparticles uptake using Sinapis alba and Lepidium sativum plants, both plant species showed uptake of considerable amounts in the roots and shoots at different concentrations [102]. In this study, both the metal salts and nanoparticles were bioavailable with no recorded phytotoxicity and the Sinapis alba plant recorded higher nanoparticles translocation with increasing concentration than Lepidium sativum.…”
Section: Noble Metal Nanoparticlesmentioning
confidence: 48%
“…The ionic form of metallic nanoparticles is commonly cited in the published literature as the likely factor attributed to the toxic effects upon biological species (Navarro et al, 2008, Xiu et al, 2012). Yet, the evidence gathered from the published literature in this study suggests that the stimulatory and inhibitory effects of metallic nanoparticles are influenced by both forms of metals depending upon the physical-chemical characteristics of nanoparticles, environmental conditions, soil media, and plant species (Asztemborska et al, 2014, Dimkpa et al, 2013, Gubbins et al, 2011, Kaveh et al, 2013, Kim et al, 2014b, Mustafa et al, 2015, Pokhrel and Dubey, 2013, Pradhan et al, 2015, Qian et al, 2013, Taylor et al, 2014, Yin et al, 2011, Yin et al, 2012.…”
Section: Comparative Effects Of Nano Versus Ionic Forms Of Metals Upomentioning
confidence: 78%
“…The growth medium was supplemented with Pt ENPs at different concentrations. (Asztemborska et al, 2014) Mn ENPs 20 15 0.05, 0.1, 0.5, 1 mg/l Seeds of mung bean were Mn ENP solutions for 4-6 h, then kept in the Petri dishes for germination in the dark. Seeds were then transferred in pots filled with perlite supplemented with Hoagland solution amended with Mn ENPs.…”
Section: Resultsmentioning
confidence: 99%
“…Feichtmeier et al [14] observed that the Au content in barley roots rose with increasing Au concentration in the nutrient medium up to 8 μg Au mL − 1 , but at the highest exposure concentration of 10 μg Au mL − 1 , slightly lower values occurred. Asztemborska et al [15] showed that the Pt content of L. sativum and S. alba shoots was clearly dependent on the Pt-NPs in the growth medium and for the highest Pt-NPs concentration applied (100 mg L − 1 ), it reached the highest level in the plants. PCA was used to investigate the effects of foliar exposure of oakleaf lettuce seedlings to M-NPs applied at different concentrations on the content of non-enzymatic antioxidants and the activity of antioxidant enzymes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Feichtmeier et al [14] noted that fresh biomass of barley decreased with increasing concentration of Au-NPs. Asztemborska et al [15] found that Lepidium sativum and Sinapis alba were able to take up Pt-NPs from the growth medium and translocate them to shoots. There is not much information about the phytotoxicity of Pt-NPs on plants, but Shiny et al [16] did not observe harmful effects of Pt-NPs on tomato and radish seeds germination.…”
Section: Introductionmentioning
confidence: 99%